2017
DOI: 10.1101/212449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processive movement of Actin by Biased Polymerization: A new paradigm of Axonal Transport

Abstract: Classic pulse-chase studies have shown that actin is conveyed in slow axonal transport, but the mechanistic basis for this movement is unknown. Recently, we reported that axonal actin was surprisingly dynamic, with focal assembly/dis-assembly events (“hotspots”) and elongating polymers along the axon-shaft (“trails”). Using a combination of live imaging, super-resolution microscopy, and modeling, here we explore how these axonal actin dynamics can lead to processive transport. We found abundant actin nucleatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Furthermore, actin patches or polarised actin networks at the axon initial segment were proposed to aid in selecting cargo for axonal transport (Watanabe et al, 2012;Balasanyan et al, 2017). Actin hotspots, trails or waves along axon shafts might mediate transport of actin (Flynn et al, 2009;Ganguly et al, 2015;Winans et al, 2016;Chakrabarty et al, 2019).…”
Section: Roles and Regulations Of The Cytoskeleton In Axonsmentioning
confidence: 99%
“…Furthermore, actin patches or polarised actin networks at the axon initial segment were proposed to aid in selecting cargo for axonal transport (Watanabe et al, 2012;Balasanyan et al, 2017). Actin hotspots, trails or waves along axon shafts might mediate transport of actin (Flynn et al, 2009;Ganguly et al, 2015;Winans et al, 2016;Chakrabarty et al, 2019).…”
Section: Roles and Regulations Of The Cytoskeleton In Axonsmentioning
confidence: 99%
“…Depletion of trails using formin inhibitors results in altered presynaptic function, suggesting that trails could shuttle actin between presynapses (Ganguly et al, 2015). Moreover, the constant growth and collapse of trails and their bias for the anterograde direction (55% against 45% retrograde) may result in the slow transport of actin along the axon (Chakrabarty et al, 2017). Indeed, classic radiolabeling studies have demonstrated that actin is transported with the SCb component of slow transport (1-4 mm/day, (Black and Lasek, 1979;Mori and Kurokawa, 1981;Willard et al, 1979), and modeling shows that biased trails-mediated transport could result in similar overall speeds (Chakrabarty et al, 2017).…”
Section: Hotspots and Trailsmentioning
confidence: 99%